Disiplin Siswa di Sekolah dan Implikasinya dalam Pelayanan Bimbingan dan Konseling - Fiana, Fani Julia; Daharnis, Daharnis; Ridha, Mursyid (Universitas Negeri Padang, 2013)
Abstract Discipline is really important to be possessed by every student. The students who are able to be discipline will obey the whole rules that have been already designed by the school. If the students can follow them successfully, a good lesson condition will be created and the students will be able to increase their achievement in learning. In fact, most of students in SMA Pembangunan Laboratorium UNP Padang could not obey the school rules, for examples, be late to school, hang out in the canteen out of school at lesson time, and at the rest time they smoke in the school canteen.The counselor teacher has given some services needed in order the students can obey the school rules. Therefore, the researcher was necessary to do a research about the students discipline in school and the implication of counseling services in SMA Pembangunan Laboratorium UNP, as a purpose to get a clear description toward the studentsâ€™ discipline performance and also the implication of counseling services. This is a descriptive research that is aimed to describe studentsâ€™ discipline at school and the implication of counseling services. The population is the whole students in grade X, XI and XII amount 671 students in SMA Pembangunan Laboratorium UNP. The sample is 73 students. The technique of data collection is questionnaires that reveal the students discipline at school, then, the data collected will be analyzed with percentage technique. The finding of the research uncover that discipline at school is in good categorize, namely, 1) tidiness discipline, 2) diligence discipline, 3) lesson time setting discipline. Whereas, discipline at school is in good enough categorize, such as, 1) cleanliness environment discipline, 2) behavior discipline. The factors supported the students discipline at school is in good categorize, like, 1) themselves, 2) contemporary friends. Whereas, the factors supported the students discipline at school is in good enough categorize.Based on the finding of the research, it is suggested to the counselor teachers to identify the causes of students discipline violation at school by giving counseling services, namely, individual counseling services and cluster counseling services, and defend the good efforts with increase the lack effort in materials, methods, media, and time of lesson guidance. Â Key word: school discipline; implication; counseling services